2010
DOI: 10.1227/neu.0b013e3181f88884
|View full text |Cite
|
Sign up to set email alerts
|

Petrous Bone Pneumatization Is a Risk Factor for Cerebrospinal Fluid Fistula Following Vestibular Schwannoma Surgery

Abstract: The higher incidence of CSF fistulas in men compared with women can be explained by means of differently pneumatized petrous bones. A high amount of petrous bone pneumatization has to be considered as a risk factor for the development of postoperative CSF fistula after vestibular schwannoma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…These air cells are of major concern in vestibular schwannoma surgery as they are known as the origin of CSF fistulae. [31] Apical cells are anatomically located anterior-medial to the internal auditory canal (IAC) and posterior medial to the carotid canal, again consistently present in group 3. These cells significantly contributed to the total volume of the temporal bone in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These air cells are of major concern in vestibular schwannoma surgery as they are known as the origin of CSF fistulae. [31] Apical cells are anatomically located anterior-medial to the internal auditory canal (IAC) and posterior medial to the carotid canal, again consistently present in group 3. These cells significantly contributed to the total volume of the temporal bone in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The pneumatized petrous apex is frequently responsible for CSF leakage after skull base surgery. Stieglitz et al showed that a 10% increase in petrous bone pneumatization increased the risk of CSF fistulae by 26% [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, postoperative CSF leak has been the most frequent serious complication in VS surgery. [45][46][47][48][49][50][51][52][53] Many reports have discussed different factors leading to postoperative CSF leaks. Pirouzmand et al 54 and Yasargil 53 suggested that hydrocephalus was the main cause of CSF leaks.…”
Section: Nonneurological Complications Csf Leakmentioning
confidence: 99%
“…48,50,57 We believe that obliteration of the opened air cells with bone wax is the most important step in avoiding CSF leak after TLAN. 26,53 Most surgeons use a dry sheet of Gelfoam to cover the dura before cement application as it facilitates graft adjustment without manipulation near the dura mater. We have used a layer of DuraGen with dural sealant before layering the temporalis fascia to ensure watertight closure.…”
Section: Discussionmentioning
confidence: 99%